Sulfur‐oxidizing bacterial populations within cyanobacterial dominated coral disease lesions. Issue 4 (22nd April 2013) - Bourne, David G.; van der Zee, Marc J. J.; Botté, Emmanuelle S.; Sato, Yui
Summary: This study investigated the diversity and quantitative shifts of sulfur‐oxidizing bacteria (SOB) during the onset of black band disease (BBD) in corals using quantitative PCR (qPCR) and cloning approaches targeting the soxB gene, involved in sulfur oxidation. Four Montipora sp. coral colonies identified with lesions previously termed cyanobacterial patches (CP) (comprising microbial communities different from those of BBD lesions), was monitored in situ as CP developed into BBD. The overall abundance of SOB in both CP and BBD lesions were very low and near the detection limit of the qPCR assay, although consistently indicated that SOB populations decreased as the lesions transitioned from CP to BBD. Phylogenetic assessment of retrieved soxB genes showed that SOB in both CP and BBD lesions were dominated by one sequence type, representing > 70% of all soxB gene sequences and affiliated with members of the Rhodobacteraceae within the α‐ Proteobacteria . This study represents the first assessment targeting SOB within BBD lesions and clearly shows that SOB are not highly diverse or abundant in this complex microbial mat. The lack of oxidation of reduced sulfur compounds by SOB likely aids the accumulation of high levels of sulfide at the base of the BBD mat, a compound contributing to the pathogenicity of BBD lesions.